Protective role of Cav-1 in pneumolysin-induced endothelial barrier dysfunction - Batori, Robert K.; Chen, Feng; Bordan, Zsuzsanna; Haigh, Stephen; Su, Yunchao; Verin, Alexander D.; Barman, Scott A.; Stepp, David W.; Chakraborty, Trinad; Lucas, Rudolf; Fulton, David J. R. (Frontiers in Immunology, 2022)
Pneumolysin (PLY) is a bacterial pore forming toxin and primary virulence factor of Streptococcus pneumonia, a major cause of pneumonia. PLY binds cholesterol-rich domains of the endothelial cell (EC) plasma membrane resulting in pore assembly and increased intracellular (IC) Ca2+ levels that compromise endothelial barrier integrity. Caveolae are specialized plasmalemma microdomains of ECs enriched in cholesterol. We hypothesized that the abundance of cholesterol-rich domains in EC plasma membranes confers cellular susceptibility to PLY. Contrary to this hypothesis, we found increased PLY-induced IC Ca2+ following membrane cholesterol depletion. Caveolin-1 (Cav-1) is an essential structural protein of caveolae and its regulation by cholesterol levels suggested a possible role in EC barrier function. Indeed, Cav-1 and its scaffolding domain peptide protected the endothelial barrier from PLY-induced disruption. In loss of function experiments, Cav-1 was knocked-out using CRISPR-Cas9 or silenced in human lung microvascular ECs. Loss of Cav-1 significantly enhanced the ability of PLY to disrupt endothelial barrier integrity. Rescue experiments with re-expression of Cav-1 or its scaffolding domain peptide protected the EC barrier against PLY-induced barrier disruption. Dynamin-2 (DNM2) is known to regulate caveolar membrane endocytosis. Inhibition of endocytosis, with dynamin inhibitors or siDNM2 amplified PLY induced EC barrier dysfunction. These results suggest that Cav-1 protects the endothelial barrier against PLY by promoting endocytosis of damaged membrane, thus reducing calcium entry and PLY-dependent signaling.